An unusual cause of dyspnea and tachycardia. Issue 9 (29th July 2016) - Reynolds, Ian S.; Coyle, Peter; Murray, Michael; Waldron, Ronan; Barry, Kevin
Key Clinical Message: Diaphragmatic hernias are typically congenital or caused by trauma. Delayed presentation is not uncommon. Repair can be undertaken through an open or minimally invasive abdominal or thoracic approach. Small defects can be repaired with sutures, while larger defects require a mesh repair. This patient's comorbidities precluded him from surgery. Abstract : Diaphragmatic hernias are typically congenital or caused by trauma. Delayed presentation is not uncommon. Repair can be undertaken through an open or minimally invasive abdominal or thoracic approach. Small defects can be repaired with sutures, while larger defects require a mesh repair. This patient's comorbidities precluded him from surgery.